2019
DOI: 10.1002/jcsm.12468
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia and ovarian cancer survival: a systematic review and meta‐analysis

Abstract: BackgroundSarcopenia is the loss of skeletal muscle mass and function that occurs with advancing age and certain diseases. It is thought to have a negative impact on survival in cancer patients. Routine computed tomography imaging is often used to quantify skeletal muscle in cancer patients. Sarcopenia is defined by a low skeletal muscle index (SMI). Skeletal muscle radiation attenuation (SMRA) is used to define muscle quality. The primary aim of this meta‐analysis was to study the association between sarcopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
105
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 46 publications
(123 reference statements)
3
105
1
1
Order By: Relevance
“…Fifteen studies6–12 20–27 were included in this systematic review, of which six studies were included in the meta-analysis 6–12. (Online supplementary Table S2 lists all excluded studies9 18 28–33 and the reasons for exclusion. )…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies6–12 20–27 were included in this systematic review, of which six studies were included in the meta-analysis 6–12. (Online supplementary Table S2 lists all excluded studies9 18 28–33 and the reasons for exclusion. )…”
Section: Resultsmentioning
confidence: 99%
“…For example, the use of bioelectrical impedance analysis to investigate whether patients’ altered body composition due to a poor nutritional status can predict the incidence of no residual disease at primary debulking and the risk of complications in patients with newly-diagnosed advanced epithelial ovarian cancer 36. Skeletal muscle mass, as assessed by CT scan analysis, is a prognostic factor independent of body mass index and is associated with the survival of ovarian cancer patients 37…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that myosteatosis, evidenced by a decrease of skeletal muscle radiodensity, was associated with adverse outcomes in various types of cancers [10,23,24]. Kroenke and colleagues demonstrated that in patients with CRC, low SMR was associated with higher overall and CRC-specific mortality [25].…”
Section: Discussionmentioning
confidence: 99%